Establishing a Hospital Pharmacy in Nepal: Experiences and Challenges - Thapa, Santosh; Palaian, Subish; Ibrahim, Mohamed Izham Mohamed (Journal of Pharmacy Practice and Community Medicine)
Hospital pharmacy in Nepal is in the state of infancy where pharmacists are struggling to gain their professional recognition. The first hospital pharmacy in Nepal was set up some 50 years ago but has not gained the popularity as this achievement was limited to some missionary hospitals. No any governmental hospitals own their pharmacy until 2015, the year in which Hospital Pharmacy Service Directive was passed which stated that every hospital should have their own pharmacy. This has given some hopes for pharmacy professionals as some of the government hospitals have already started running their own pharmacy and stopped renting the pharmacy space on contract. However, multiple challenges exists in setting up a hospital pharmacy and expand the services for the care of patients, some private hospitals have run a well-functioning pharmacy unit on its own. Some of these hospitals have delivered good pharmacy services like use of computerized billing system, dispensing and counseling by qualified pharmacy personnel, drug information. Involvement of dedicated manpower and support from the hospital management are equally important for the smooth running of hospital pharmacy.
Keywords: Challenges; Experiences; Hospital pharmacy; Nepal; Rational drug use